Three Poems by Victoria Kennefick - Kennefick, Victoria (ABEI Journal, 2021)
“Selfie,” “Smell Dating,” and “Hunger Strikes Victoria Kennefick” are part of the collection Eat Or We Both Starve (2021) by Victoria Kennefick, published by Carcanet Press. All rights reserved. https://www.carcanet.co.uk/cgi-bin/indexer?product=2363